Communication Strategies as Key of Change Leadership - Marjanović, Milena (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The purpose of this study is to investigate the impact of internal marketing communication strategies and employer branding approaches on strategic human resource management, as well as their effect on organizational change management. This will be achieved using a holistic narrative approach to research, examining current market trends, relevant and available scientific literature, and a case study on acquisitions of retail chains. The aim of the study is to develop a conceptual model of organizational change management based on communication strategies. The findings suggest that the developed conceptual model creates the necessary prerequisites and significantly influences the encouragement of effective leadership during changes, as well as reducing employee resistance in the process of implementing organizational changes. Also, this study offers a deeper understanding and supports decision-makers, while encouraging further research by scholars. However, it is limited by the descriptive approach, the limited availability of literature, and the small sample size.